Time Management DVD based training program - Fenman (Fenman Fenman, 2007)
Time works a little like a bank. Every time you are credited with 480 minutes in an eight-hour work day, or 1,440 minutes every 24 hours. Every night whatever time you have failed to invest in a good purpose is lost. Time cannot carry a balance forward and it does not allow overdrafts. Each new day it opens a new account with you, and each night it burns the record for the day.
includes participant's work book and facilitator's guide.
Keywords: Time management